Dynamics of CSR and Employee Retention: A Generational Perspective - Lee, C. Christopher; Hwang, David; Acharya, Keshab (STIE Malangkucecwara, 2025)
The main objective of this study is to gain insights into the five corporate social responsibility (CSR) factors— environment-related CSR, human rights & labor, product responsibility, community engagement, and corporate governance— and to understand their impact on employee retention among gen X, Y, and Z employees in the workplace during the Covid-19 pandemic. We collected survey data using Amazon Mechanical Turk, with a final sample size of 536 responses. The regression analyses indicated a positive and significant relationship between environment-related CSR and employee retention. The results also suggested that both human rights and labor-related CSR, as well as product responsibility-related CSR, are positively related to higher employee retention. Additionally, generational differences moderated the effect of environment-related CSR on employee retention, with a stronger correlation observed among gen Y and Z employees compared to gen X. These findings help reconcile mixed evidence on CSR–retention links by emphasizing generational differences and offering practical guidance. Managers aiming to retain talent should prioritize environmental stewardship, fair labor practices, and responsible products while tailoring CSR initiatives to the preferences of different employee cohorts.